Acute HIV Infection Results in Subclinical Inflammatory Cardiomyopathy. (28th March 2018) - Schuster, Christopher; Mayer, Florian J; Wohlfahrt, Corinna; Marculescu, Rodrig; Skoll, Michael; Strassl, Robert; Pavo, Noemi; Popow-Kraupp, Theresia; Hülsmann, Martin; Bauer, Martin; Aichelburg, Maximilian C; Rieger, Armin; et al.
Abstract : During acute human immunodeficiency virus (HIV) infection, a functional and morphological myocardial impairment fueled by inflammatory activation and extensive viral replication was found, resulting in a reversible subclinical inflammatory cardiomyopathy and perhaps representing the cornerstone of progressive myocardial damage in HIV-infected individuals. Abstract: The impact of excess viral RNA on myocardial function and morphology in the setting of acute human immunodeficiency virus (HIV) infection remains unknown. In this study, 49 patients with acute HIV infection showed increased levels of N-terminal prohormone of brain natriuretic peptide, a surrogate of myocardial function, which decreased with viral suppression and normalization of systemic inflammation (79 pg/mL vs 28 pg/mL; P < .001). A comparable change was seen with levels of troponin T, a marker of morphologic myocardial damage (4.9 ng/L vs 1.5 ng/L; P < .001). In conclusion, we observed significant functional and morphological myocardial impairment during acute HIV infection, fueled by inflammatory activation and extensive viral replication, resulting in a reversible subclinical inflammatory cardiomyopathy.